Sex and Age Dependencies of Aqueductal Cerebrospinal Fluid Dynamics Parameters in Healthy Subjects - Sartoretti, Thomas; Wyss, Michael; Sartoretti, Elisabeth; Reischauer, Carolin; Hainc, Nicolin; Graf, Nicole; Binkert, Christoph; Najafi, Arash; Sartoretti-Schefer, Sabine (Frontiers in Aging Neuroscience, 2019)
Objectives To assess the influence of age and sex on ten cerebrospinal fluid (CSF) flow dynamics parameters measured with an MR phase contrast (PC) sequence within the cerebral aqueduct at the level of the intercollicular sulcus. Materials and Methods 128 healthy subjects (66 female subjects with a mean age of 52.9 years and 62 male subjects with a mean age of 51.8 years) with a normal Evans index, normal medial temporal atrophy score (MTA) and without known disorders of the cerebrospinal fluid circulation were included in the study. A phase contrast MR sequence on a 3T MR scanner was used. Ten different flow parameters were analyzed using postprocessing software. Ordinal and linear regression models were calculated. Results The parameters stroke volume (sex: p<0.001, age: p=0.003), forward flow volume (sex: p<0.001, age: p=0.002), backward flow volume (sex: p<0.001, age: p=0.018), absolute stroke volume (sex: p<0.001, age: p=0.005), mean flux (sex: p<0.001, age: p=0.001), peak velocity (sex: p=0.009, age: p=0.0016) and peak pressure gradient (sex: p=0.029, age: p=0.028) are significantly influenced by sex and age. The parameters regurgitant fraction, stroke distance and mean velocity are not significantly influenced by sex and age. Conclusions CSF flow dynamics parameters measured in the cerebral aqueduct are partly age and sex dependent. For establishment of reliable reference values for clinical use in future studies, the impact of sex and age should be considered and incorporated.